Threeyasa Group Banyuwangi Company Profile Design - Shevti Arbekti Arman; Yuanyuan Wang; Guijiao Zou (Journal of Computer Science Advancements, 2023)
In this era of industrial revolution, it is undeniable that development progress is increasing to meet human needs in carrying out their activities. One of the groups that play an important role in this field is a company that focuses on tourism services. ThreeYasa Group is a Travel Agency business that was founded in 2020. Threeyasa Group is still fairly conventional in conducting promotions and communication with customers, namely utilizing the exchange of short messages only. ThreeYasa Group needs a digital platform to introduce its business to a wider audience. Company Profile is an effective promotional media design that can attract consumer attention and build cooperation with business people. Designing a company profile can make it easier for the owner to manage his business and make his business more dynamic. software development in making a company profile using the waterfall model. system analysis using interviews and observation methods. in visualizing actors with the system using usecase diagrams implemented using StartUML software. while coding uses the php programming language with Notepade++ software. Testing the system using Black Box Testing.